1997
DOI: 10.1084/jem.185.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Respiratory Burst in X-linked Chronic Granulomatous Disease Mice Leads to Abnormalities in Both Host Defense and Inflammatory Response to Aspergillus fumigatus

Abstract: Mice with X-linked chronic granulomatous disease (CGD) generated by targeted disruption of the gp91phox subunit of the NADPH–oxidase complex (X-CGD mice) were examined for their response to respiratory challenge with Aspergillus fumigatus. This opportunistic fungal pathogen causes infection in CGD patients due to the deficient generation of neutrophil respiratory burst oxidants important for damaging A. fumigatus hyphae. Alveolar macrophages from X-CGD mice were found to kill A. fumigatus conidia in vitro as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
275
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(295 citation statements)
references
References 45 publications
17
275
1
2
Order By: Relevance
“…In the context of the autoimmune attack in MS, ROS generation induced by phagocytosis of myelin debris may represent a negative feedback loop to self-limit cytokine-driven neuroinflammation. This view correlates with previous observations that the genetic defect of p47-PHOX enhances autoimmune encephalomyelitis and arthritis in animal models (Hultqvist et al, 2004) and leads to chronic non-infectious inflammation in chronic granulomatous disease (Morgenstern et al, 1997). Additional support for this hypothesis comes from a recently published study showing that p47-PHOX-mediated ROS negatively regulate expression of IL-8 and IL-1␤ in human neutrophils (Lekstrom-Himes et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…In the context of the autoimmune attack in MS, ROS generation induced by phagocytosis of myelin debris may represent a negative feedback loop to self-limit cytokine-driven neuroinflammation. This view correlates with previous observations that the genetic defect of p47-PHOX enhances autoimmune encephalomyelitis and arthritis in animal models (Hultqvist et al, 2004) and leads to chronic non-infectious inflammation in chronic granulomatous disease (Morgenstern et al, 1997). Additional support for this hypothesis comes from a recently published study showing that p47-PHOX-mediated ROS negatively regulate expression of IL-8 and IL-1␤ in human neutrophils (Lekstrom-Himes et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Genetic mutations in NOX2 (gp91phox), p47phox, p67phox and p22phox are known to be responsible for development of CGD, but minimal evidence exists for associations of these polymorphisms with other diseases, and a recent analysis failed to show an association of polymorphisms within gp91phox, p47phox, p67phox or p22phox with infectious or non-infectious lung diseases, such as tuberculosis or sarcoidosis (199). Attempts to implicate NOX2 or p47phox in models of lung inflammation and injury, using gp91phox−/− or p47phox−/− mice, demonstrated that genetic NADPH oxidase deficiency was in many cases associated with enhanced inflammation and injury (200)(201)(202)(203), implicating that NOX2 also has beneficial functions in regulating inflammatoryimmune responses. For example, infection of gp91phox−/− mice with the yeast C. neoformans or with influenza virus was in either case found to result in increased Th1-skewed inflammation and granuloma formation, compared to their wild-type counterparts, which led to increased influenza clearance and protection against C. neoformans infection (204,205).…”
Section: Nox2mentioning
confidence: 99%
“…The superoxide generated by the phagocyte NADPH oxidase exhibits potent antipathogenic actions, mediating the destruction of a host of invading microorganisms. Furthermore, superoxide can subsequently be converted to a vast array of other reactive oxygen species (ROS) that are detrimental to the invading organism (9,10). The critical role fulfilled by ROS species in the control of pathogen burden is made clearly apparent by the genetic condition chronic granulomatous disease (CGD), characterized by deficiency of a functional phagocytic oxidase, and greater susceptibility to infection with bacterial and fungal pathogens (9,11).…”
Section: T He Encapsulated Budding Yeast Cryptococcus Neoformansmentioning
confidence: 99%